2007
DOI: 10.1007/s11556-007-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multimodal activation program (SimA-P) in residents of nursing homes

Abstract: Is it possible to maintain or even enhance functional and cognitive independence in residents of nursing homes? Little is known about the potentials and limits of therapeutic methods designed to maintain independence in elderly people already in need of residential nursing care. The aim of the "Rehabilitation in Nursing Homes" research project was to determine the practicability and effectiveness of a rehabilitative approach targeting residents of nursing homes. The main objectives of the activation program we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Of the 21 group studies, 17 (81%) reported pre–post-test scores using the Mini Mental State Examination (MMSE), the Chinese MMSE or the 7MST (7 Minute Screening Test), and could therefore be included in an effect size (ES) analysis (Figure 2). Oswald et al. (2007) uniquely included a staff survey on residents’ cognitive change.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 21 group studies, 17 (81%) reported pre–post-test scores using the Mini Mental State Examination (MMSE), the Chinese MMSE or the 7MST (7 Minute Screening Test), and could therefore be included in an effect size (ES) analysis (Figure 2). Oswald et al. (2007) uniquely included a staff survey on residents’ cognitive change.…”
Section: Methodsmentioning
confidence: 99%
“…Han et al (2017) was the only double-blind or cross-over trial. Three were conducted across multiple centres: Graessel et al (2011) and Oswald, Gunzelmann, and Ackermann (2007) in German nursing homes, and Serda`i Ferrer and del Valle (2014) in Spanish day hospitals. For characteristics of all studies, see Tables 3 to 5.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…3 Some evidence shows that physical training and targeted strength, stamina, suppleness, coordination and cognitive activation have positive effects on falls prevention and balance in individuals with dementia. 23,24 However, these trials were smallscale studies and the effectiveness of falls prevention in individuals with dementia has yet to be determined. 25 Encouraging mobility and exposure to risky situations in less physically able individuals through balance interventions can be counterproductive to falls reduction.…”
Section: Discussionmentioning
confidence: 99%